A Microporous Co(II)‐Based 3‐D Metal Organic Framework Built from Magnetic Infinite Rod‐Shaped Secondary Building Units. Issue 38 (10th October 2019) - Kourtellaris, Andreas; Moushi, Eleni E.; Spanopoulos, Ioannis; Trikalitis, Pantelis N.; Pissas, Michael; Papaefstathiou, Giannis S.; Sanakis, Yiannis; Tasiopoulos, Anastasios J.
Abstract: Invited for the cover of this issue is Anastasios Tasiopoulos from the University of Cyprus. The cover image shows photos from the southwestern Cyclades island group of the Aegean Sea, which contain a wealth of minerals and rocks. Some of these exhibit porous structures and interesting magnetic properties. Abstract : The combination of aesthetic beauty and notable physical properties similar to the Cyclades Islands also appears in our reported metal organic framework . Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by Tasiopoulos et al.